Optimal protection relay coordination for overcurrent relays in radial system / Mohd Azri Kasdi - Mohd Azri, Kasdi (2018)
Increase in demand on electrical power supply requires reliable and sustainable electrical system. Therefore, suitable design of power system and having a reliable and robust power system design for electrical network are crucial to minimize the possibility of any power downtime and disturbances. Unnecessary power interruption could happen in the large electrical network due to disturbances or faults that occurred far away from the healthy system. Thus, one of the mitigation is to have proper coordinated relay protection system in power network. Relay protection system is crucial to ensure equipment and system which located outside from zone of protection are protected and safe to operate continuously during fault happen in other system in the same network. The main objective of this research is to perform overcurrent relay protection coordination to obtain an optimum relay setting to minimize the operating time of overall relays in the network. The optimum value of time multiplier setting (TMS) is determined based on predefined value of tap setting (TS) and plug setting multiplier (PSM). The studies are conducted by using MATLAB software to implement the optimization method using Particle Swarm Optimization (PSO). The result from an optimization method then is compared with conventional relay coordination method for electromechanical relay as study case. The algorithm is applied for radial network. The results of the studies performed will be useful to select the best relay setting in order to optimize the design and to achieve reliable electrical network.